2016
DOI: 10.1016/j.biomaterials.2016.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Human relaxin gene expression delivered by bioreducible dendrimer polymer for post-infarct cardiac remodeling in rats

Abstract: In consensus, myocardial infarction (MI) is defined as irreversible cell death secondary to prolonged ischemia in heart. The aim of our study was to evaluate the therapeutic potential of anti-fibrotic human Relaxin-expressing plasmid DNA with hypoxia response element (HRE) 12 copies (HR1) delivered by a dendrimer type PAM-ABP polymer G0 (HR1/G0) after MI on functional, hemodynamic, geometric, and cardiac extracellular matrix (ECM) remodeling in rats. HR1/G0 demonstrated significantly improved LV systolic funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…The injection of erythropoietin or GM-CSF is currently performed to treat anemia and granulocytopenia, respectively. Currently, expensive protein replacement is used; however, if safe and effective nonviral vectors can be developed, then nonviral gene therapy might prove to be a more economical approach [ 86 , 87 ]. In general, we feel that the development of nonviral vectors could enable gene therapy to be the method of choice for a variety of diseases treated in the clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…The injection of erythropoietin or GM-CSF is currently performed to treat anemia and granulocytopenia, respectively. Currently, expensive protein replacement is used; however, if safe and effective nonviral vectors can be developed, then nonviral gene therapy might prove to be a more economical approach [ 86 , 87 ]. In general, we feel that the development of nonviral vectors could enable gene therapy to be the method of choice for a variety of diseases treated in the clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…The NPs were shown to significantly improve LV systolic function after MI in rats as well as showed favorable post-infarct cardiac ECM remodeling. 111 In a more recent study, Zhu and coworkers constructed lipid nanoparticles containing lncRNA– Tcf21 antisense RNA inducing demethylation (TARID) to target myocardial fibrosis. The authors first demonstrated the potential effects of Tcf21, which is derived from mesenchymal stem cell–derived extracellular vesicles (EVs) for cardiac remodeling.…”
Section: Nanomedicine Mediated Therapeutics Strategies For MImentioning
confidence: 99%
“…For heart-related applications, perfusing dendrimers carrying the β-galactosidase gene into the coronary artery led to protein expression in myocytes for 7-14 days (Wang et al, 2000). In addition, intramyocardial injection of dendrimers carrying the relaxin gene promoted left ventricular systolic function in rats model of myocardial infarction (Lee et al, 2016). Notably, long-term delivery of PAMAM impaired the recovery of cardiac function after ischemia/reperfusion in rats (Babiker et al, 2020).…”
Section: Dendrimersmentioning
confidence: 99%